The Influence of Training and Career Development on Public Elementary School Teacher Performance - Septian, Andhika Rully; Andayani, Sri (Universitas Sang Bumi Ruwa Jurai, 2024)
This study aimed to examine the effects of training and career development on the performance of teachers at State Elementary School 2 Dono Arum, Central Lampung Regency. Training for agencies was conducted to increase productivity, while training for employees aimed to improve performance, as individuals need to continuously learn and practice to develop the competence and skills required for their jobs. Career development was also essential, as employees not only sought to maintain their current positions but also expected growth, progress, and opportunities for advancement. The analytical tools used in this study included validity tests, reliability tests, normality tests, multiple linear regression analysis, and determination coefficient tests. The results indicated that: (1) training (X1) had a significant effect on teacher performance (Y), 2) career development (X2) also significantly influenced teacher performance, and 3) both training and career development together had a significant impact on the performance of teachers at State Elementary School 2 Dono Arum.